Academic Language, Power and the Impact of Western Knowledge Production on Indigenous Student Learning - O'Brien, Karen (The Australian Journal of Indigenous Education, 2008)
Abstract This paper explores the prescriptive, distancing and separating qualities that exist in Western systems of knowledge production. It examines scientific language and how discrimination takes place in the university setting and explores the ways in which academic knowledge production affects the learning experiences, participation and completion rates of Indigenous students. It suggests improving teaching and learning strategies to enhance unacknowledged learning processes towards providing inclusive learning practices, and to strengthen educational outcomes for Indigenous students with the prospect of improving their completion rates at universities.